Hormonal response of elite swimmers to overtraining - Hooper, S. L.; MacKinnon, L. T.; Gordon, R. D.; Bachmann, A. W. (Medicine & Science in Sports & Exercise, 1993)
Elite Australian swimmers (N = 14) had measurements of stress hormones taken at early-, mid-, late-season, during taper, and 1-3 days after trials. Training details and subjective ratings of fatigue were recorded daily. No significant differences were seen in norepinephrine or cortisol concentrations between the times. Symptoms of overtraining were identified in three of the athletes, based on performance deterioration and high prolonged levels of fatigue. In each swimmer norepinephrine levels were higher than non-stressed swimmers from the mid-season on. They were significantly higher during taper. [Overtrained swimmers did not respond to the taper whereas the others did.] Implication: Norepinephrine could provide a useful marker for overtraining.